Аналіз засобів формування сигналів - Томилов, Д. О. (My University, 2018)
To convert a sampled signal into analogue form, suitable for processing analogue devices (amplifiers and filters) and subsequent reproduction through acoustic systems, is a digital-to-analog converter (DAC). The transformation process is a reverse sampling process: having information about the size of the reference (amplitude of the signal) and taking a certain number of readings perunit of time, an interpolation restores the output signal.
Keywords: звук; аудіо